Hubungan Pembelajaran Secara Daring Dengan Minat Belajar Di Masa Pandemi Covid 19 di Universitas Kristen Palangka Raya - Yemima Yemima; Ricke Marianty; Kristina Kristina (FKIP, Universitas Palangka Raya, 2022)
The purpose of this study was to determine the relationship between online learning and interest in learning during the covid 19 pandemic at Palangka Raya Christian University. The respondents in this study were students at the Christian University of Palangka Raya. The data collection technique used in this study was a questionnaire using the google form application. The analytical method used is simple linear regression analysis. The results of this study indicate that online learning has a significant influence on student interest in learning at Palangka Raya Christian University, the relationship between online learning and student interest in learning at Palangka Raya Christian University is positive and strong and the relative contribution of online learning to learning interest is 38.1%.